Study of Vehicle Movement for Mixed Traffic Modeling Using Social Force Model - Rina Mardiati (Proceeding of the Electrical Engineering Computer Science and Informatics, 2015)
Today, many models for describing vehicle movementhave been developed. Most of the available methods for modelingthe vehicle movement in traffic assume that vehicles move on lanesdisciplines. Meanwhile, in developing countries the traffic washeterogeneous, which means there are many types of vehicles. Indeveloping countries, each vehicles usually did not move based onlane disciplines, they move irregularly with unpredictable behavior.The vehicles used to move based on the empty space around themin order to make their travel time faster. Lately, research onmodeling the irregular movement of vehicle using Social ForceModel approached have been developed, especially for mixedtraffic condition in developing countries. This paper will explainabout the basic concept of Social Force Model theories and also willgive a review and comparison of existing the vehicle movementmodel using Social Force Model in mixed traffic condition. Basedupon the review and comparison, some practical issues such asadding some new parameters (driver’s psychology, crowd situationfactor, environmental, driver distraction, etc.) to improve theaccuracy and reliability of vehicle movement model will bepresented as a contribution from this paper.